2021
DOI: 10.3389/fonc.2021.580220
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Early Death in Patients With Localized Nasopharyngeal Cancer: A Population-Based SEER Analysis

Abstract: Localized nasopharyngeal cancer (NPC) is a highly curable disease, but the prognosis of certain cases is still poor. Distinguishing patients with a poor outcome is necessary when developing therapeutic strategies. The aim of this study was to investigate the characteristics of early death (ED) among patients with localized NPC, and to identify independent predictors of ED. Patients diagnosed with localized NPC were included from the Surveillance, Epidemiology, and End Results dataset, and univariate and multiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Exploring relevant factors can help clinicians identify high-risk patients and develop targeted treatment plans to improve the survival rate and quality of life of patients . Existing evidence has found that risk factors for early death could be identi ed in gastric cancer (Zhu et al 2020), endometrial cancer (Song, Wang, Zhou and Zhang 2020) and nasopharyngeal cancer (Chen et al 2021), but the results on SCLC cases were rarely reported. Therefore, it is practical and necessary to identify risk factors for early death in SCLC.…”
Section: Introductionmentioning
confidence: 99%
“…Exploring relevant factors can help clinicians identify high-risk patients and develop targeted treatment plans to improve the survival rate and quality of life of patients . Existing evidence has found that risk factors for early death could be identi ed in gastric cancer (Zhu et al 2020), endometrial cancer (Song, Wang, Zhou and Zhang 2020) and nasopharyngeal cancer (Chen et al 2021), but the results on SCLC cases were rarely reported. Therefore, it is practical and necessary to identify risk factors for early death in SCLC.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, predictive factors associated with early mortality in malignant tumors such as breast, liver, nasopharyngeal, esophageal, and gastric cancers have been reported. [10][11][12][13][14]19] However, there are fewer studies on early mortality in elderly SCLC patients.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, early death (defined as death occurring within 3 months after initial diagnosis) of cancer patients is a very objective clinical feature revealing the aggressiveness of cancer. Researchers have reported predictive factors associated with early death in malignancies such as breast, liver, nasopharyngeal, esophageal, and gastric cancers, [10][11][12][13][14] however, risk factors for early death in elderly SCLC patients remain unreported.…”
Section: Introductionmentioning
confidence: 99%
“…By integrating variables identified to have a significant impact on outcome, nomograms are excellent visualization tools for the estimation of survival rates, but also identify the critical parameters responsible for survival (15). Reported studies examining into some specific subgroups of NPC, including some tumor stage (16)(17)(18)(19)(20)(21)(22), patient age (20,(23)(24)(25)(26), histologic type (27)(28)(29) and even race (30)(31)(32), in a wide scope based on the Surveillance, Epidemiology, and End Results (SEER) data, have shown the potential and ability to provide a better reference for clinical decisions (16,21,23). However, few studies have specifically focused on LA-NPC patients as a group using the SEER data.…”
Section: Introductionmentioning
confidence: 99%